The impact of nurses' perceptions of systems thinking on occurrence and reporting of adverse events: A cross‐sectional study. (25th January 2022) - Kakemam, Edris; Albelbeisi, Ahmed Hassan; Davoodabadi, Samane; Azarmi, Mina; Zolghadr, Fatemeh; Mamene, Mehdi
Abstract: Aims: To assess systems thinking level and its relationship with occurrence and reporting of adverse events in Iranian nurses. Background: Systems thinking has recently emerged as an important element of patient safety and quality improvement in health care systems. It helps health care professionals to understand the different elements of health care systems, the interrelatedness and interdependencies of these elements in the health care systems. Methods: This cross‐sectional survey was carried out in 10 teaching hospitals in Tehran, Iran. A total of 511 nurses were selected using simple random sampling. Systems thinking was measured using the validated Systems Thinking Scale. Data analysis was performed by descriptive analyses, independent t test and logistic regression analysis. Results: The average score for total systems thinking was a mean of 49.45 (SD = 12.10; range 0–80). In total, 67.5% of participants reported the experience of the occurrence of adverse events leading to harm to patients, and 65.2% of them responded as having appropriate adverse events reporting behaviours. Nurses who had higher scores in systems thinking were found to be more likely to report adverse events (odds ratio = 1.07; 95% CI = 1.05–1.09), whereas they were less prone to experience adverse events (odds ratio = 0.97; 95% CI = 0.95–0.98). Conclusion: Our results indicated that the nurses' systems thinking level was moderate. Systems thinking had a significant role in preventing the occurrence of adverse events as well as improving the reporting of adverse events. Therefore, it is recommended to enhance the competency of nurses' systems thinking to prevent the occurrence of adverse events and to improve the reporting of adverse events. Implications for nursing management: Nursing managers need to focus on the systems thinking weaknesses and the occurrence and the reporting of adverse events in policymaking, practice and research. Also, systems thinking should be integrated with the health care system for preventing the occurrence of adverse events and improving reporting of adverse events. They should support, lead and allocate the essential pragmatic strategies and resources for the involvement of all health care members in policymaking.